Long-term water sorption/solubility of two dental bonding agents containing a colloidal dispersion of titanium dioxide - Mohammed Ali Fadhil Al-; Rafid Jihad Al-Badr; Muaid S Abbas Shamash (Wolters Kluwer Medknow Publications, 2023)
The aim was to analyze the influence of the incorporation of 4% by mass of colloidal dispersion of titanium dioxide (TiO2) nanoparticles on the long-term water sorption and solubility of two commercial universal bonding agents. In vitro studies. A colloidal dispersion of TiO2 nanoparticles was formulated and blended into two commercial dental bonding agents, i.e., Ambar Universal (FGM, Brasil) and G-Premio Bond Universal (GC, America) at 4% by mass. Forty bonding agent discs were fabricated and segregated into four bonding agent groups of 10 discs each, i.e., GA: Ambar Universal (control), GB: Ambar Universal (4% TiO2 incorporated), GC: G-Premio Bond universal (control), and GD: G-Premio Bond (4% TiO2 incorporated). The bonding agent discs were developed by dispensing the bonding agents into a silicone cast of 5 mm diameter and 1 mm depth. After bonding agent discs were desiccated, the cured discs were weighed and kept in distilled water to be evaluated for water sorption and solubility over 1 year storage period. Statistical analysis was performed by independent variable t-test performed using the IBM SPSS software (Chicago, IL: SPSS Inc). The incorporated bonding agent groups (GA and GB) showed significantly lower (P < 0.05) water sorption and solubility following 1 year of water storage in comparison to the control bonding agents. Both GC and GD demonstrated remarkably lower water sorption and solubility than GA and GB. Incorporation of the colloidal dispersion of TiO2 nanoparticles at 4% by mass into the universal bonding agents has significantly reduced their water sorption and solubility contrast to their control groups.